A world free from nuclear weapons : the Vatican conference on disarmament - Christiansen, Drew; Sargent, Carole (Georgetown University Press, 2020)
"In November 2017 Pope Francis made the first declaration in the nuclear area rejecting the possession of nuclear weapons, even as a form of deterrence. To set the stage for this statement, he hosted a conference at the Vatican. Under the leadership of Cardinal Turkson, a charismatic priest from Ghana and potential future pope, religious and secular leaders came together, from representatives of NATO and Russia to members of ICAN who had just won the Nobel Peace Prize, to make an historic statement about the unacceptability of nuclear arms. One of the last speakers was a hibakusha, a survivor of Hiroshima. This book collects the official statements made during that conference. Beginning with Francis' own words, it includes contributions from Nobel Laureates Paolo Cotta Ramusino, Muhammad Yunus, Mohamed El Baradei, and Mairead Maguire, as well as essays by Cardinal Turkson and Nato Deputy Secretary General Rose Gottemoeller"--